Jovem conectado: influências identitárias - Gonçalves, Luis Fernando [UNESP] (2014)
The changes in contemporary society have been analyzed by various disciplines in the field of Humanities, trying to understand its implications for individuals and their social relationships. Here are some possible theoretical links between the concepts identity and seek to relate them to the main influences and outcomes observed in the identity influences young people from a specific region of São Paulo State process, always considering the contemporary social scene. We discuss from different social theories and their linkage with the concept of identification, emphasizing its procedural dimension. Because we understand that work in contemporary capitalism, assumes settings such as flexibility, temporality, precariousness, informality, producing changes that are expressed in the mode of being of workers, we believe that young people online will suffer from the same identity influences. Our reflections on the contemporary production context lead us to say that, despite the difficulties, the construction of identity processes in the subjects still takes place. Surely positions are transitory and ephemeral subjects, but you can not deny the coherence and continuity in the life history of each. We try to baste the data collected from questionnaires and focus analysis, a media room, and from this we find evidence to suggest such identity constructions, always supported the point of view of the young connected, which is the focus of our attention and study. Thus, we realize that we are facing another cultural sketch that reveals the strength of human relationships, be they virtual or real: the influence of identity is revealed in these kids connected as a direct and relevant to their existence in the Contemporary World production. This demonstrates the power of social networks in the formation of man, and more than that, points to current and innovative directions that deserve attention and assertive looks of educators, parents and leaders